Sir John Franklin and the Arctic Regions - Simmonds, Peter Lund (Cambridge University Press, 2012)
In May 1845, the famous Arctic explorer John Franklin (1786–1847) embarked on another attempt to find the elusive North-West Passage. He never returned from this voyage, and was last seen by whalers in Baffin Bay in July 1845. Some thirty rescue missions were launched between 1847 and 1859 to find the missing men. Franklin was not the first explorer to make the dangerous voyage to find the route connecting the Atlantic and Pacific, and journalist Peter Lund Simmonds (1814–97) draws from a wide range of reports and publications about these expeditions in his history of the search for the North-West Passage, published in 1851. The detailed account also includes descriptions of the many missions to find Franklin, and this second edition was published later in the same year as the first in order to include updated reports on the progress of his rescue.